Do Those Diagnosed with Alzheimer's Disease Lose Their Souls? Whitehead and Stengers on Persons, Propositions and the Soul. Issue 4 (November 2016) - Halewood, Michael
In this article, I use the work of Alfred North Whitehead and Isabelle Stengers to challenge the biomedical and commonsense view that those diagnosed with Alzheimer's disease suffer an irreparable and inevitable loss of self and that this loss is inextricably tied to a decline in linguistic capability which itself bears immediate witness to a deterioration in the brain. Through an analysis of Whitehead's (1933, 1938 ) provocative conceptualization of the soul, andStengers' (2005) reading of this, I suggest that it is possible to dislocate language from its supposed position as that which produces and fully expresses human experience. This involves a challenge to the 'linguistic turn' as to be found in much contemporary social theory, philosophy and social psychology. The discussion of Whitehead's (and Stengers') ideas regarding the soul involves a reading of Whitehead's notions of 'propositions', 'contrasts' and the 'social environment'. Through these analyses, I seek to relocate the problem of language and identity and its relation to Alzheimer's disease. I go beyond any reduction of the problem either to its social component, where the self is seen as a resolutely human 'person', or to its natural element, where Alzheimer's disease is seen solely as a problem located within the brain. Instead, I try to think the natural and social together. My aim is not to explain away the problem but to suggest a more productive way of thinking about those diagnosed with Alzheimer's disease, and ourselves.